Strategies to Improve Engagement of Latino Adolescents in Mental Health Research - Allison McCord Stafford; Camila A. Pulgar; Tatiana Villarreal‐Otálora (Mental Health Science)
ABSTRACT While Latino adolescents of all genders in the US experience inequities in depressive symptoms, suicide attempts, and access to mental health services in comparison to non‐Latino White peers, they are underrepresented in adolescent mental health research. Additionally, little has been written on how to best engage Latino adolescents in mental health research. Given that this population has unique developmental and cultural needs, our purpose is to outline strategies for increasing engagement of Latino teens in mental health‐focused studies based on lessons learned from three investigators’ programs of research. This manuscript describes the research programs of three bilingual investigators who have dedicated their research careers to addressing mental health inequities of Latino adolescents. We synthesize lessons learned across all aspects of study design, focusing on recommendations to facilitate the engagement of Latino adolescents in mental health research. Based on the successes and challenges in our programs of research, we provide four key recommendations to increase engagement of Latino adolescents in mental health research: (1) Become knowledgeable about the values, culture, and language of the local Latino community; (2) Consider recruitment strategies that are inclusive of both clinical and community Latino teen samples; (3) Balance the autonomy of the Latino teen with family values throughout the research process; and (4) Offer flexible data collection options knowing that teens and parents may have various levels of comfort with sharing information about themselves and their mental health. Researchers can build upon the lessons from our combined almost 40 years of research experience with Latino adolescents, emerging adults, and parents. Through consideration of these recommendations, the recruitment of diverse groups of Latino teens into mental health research can be bolstered with the goal of generating translatable knowledge to help address mental health inequities faced by this population.